Further results on differential inequality of a class of second order neutral type - Wang, Peiguang; Wu, Yonghong (Tamkang Journal of Mathematics, 2004)
In this paper, we develop several new results related to the nonexistence criteria for eventually positive solutions of a class of second order neutral differential inequalities with distributed deviating arguments. The work generalizes various existing result.